Heroic forms : Cervantes and the literature of war - Rupp, Stephen James (University of Toronto Press, 2014)
In Cervantes and the Literature of War, Stephen Rupp connects Cervantes's complex and inventive approach to literary genre and his many representations of early modern warfare.